ANALISIS TEOLOGIS LAMBANG SALIB KRISTUS YANG SESUAI DENGAN ALKITAB DAN PENGGUNAANNYA BERDASARKAN YOHANES 19:17-25 DI GMAHK JEMAAT RAWAMANGUN JAKARTA TIMUR - Denny Austin Panjaitan; Milton T. Pardosi (Jurnal Koinonia, 2017)
The purpose of this research is to know the understanding about the cross of Christbased on John 19:17-25. This research was focused on Rawamangun CongregationChurch, East Jakarta.This research has three main basic indicators, the definition of the cross of Christbased on the Greece as the original language in the New Testament, the cause achange of the cross in Christianity and the use of symbol of cross that isincompatible with the Bible especially that derived from paganism.This research is divided into two parts, theoretical research and field research. Theresult of the theoretical research is about the notion of the cross of Christ based onGreek as the original language of the New Testament Bible, the cause a change ofthe cross in Christianity and the usage of the cross which is incompatible with theBible, especially from the unbelief.This research consisted of three parts: (1) What is the original word of cross in theBible? Some experts stated that the word of cross in the Bible originated from theword ‘stauros’ and ‘xulon.’These words have similar meaning that is a stud insteadof cross; (2) Definition of the cause a change of the cross in Christianity. Expertsstated that cross is a religious symbol that existed before the Christianity appeared.The symbol of cross is not used by the early church. Until to the 3rd century,Constantine, sun worshiper, brought symbol of the cross to Christianity as his statedvow, and; (3) The use of symbol of cross that is incompatible with the Bibleespecially that derived from paganism is something that is not very relevant becausecross is not a tool that is charged to Christ, then His people also do not use and lift upthe death tool that actually was not charged to Christ.The result of this research by using questionnaire that was shared to 40 GMAHKmembers of Rawamangun Congregation, where this questionnaire consisted of 24statements, yielded a data that can be concluded that the respondents have a goodunderstanding in answering the indicators. This happened because before theresearcher shared the questionnaire, firstly, the researcher explained about this lessonin a seminar.